Thirty shades of truth: conspiracy theories as stories of individuation, not of pathological delusion - Raab, Marius H.; Ortlieb, Stefan; Auer, Nikolas; Guthmann, Klara; Carbon, Claus-Christian (Frontiers in Psychology, 2013)
Recent studies on conspiracy theories employ standardized questionnaires, thus neglecting their narrative qualities by reducing them to mere statements. Recipients are considered as consumers only. Two empirical studies―a conventional survey (n=63) and a study using the method of narrative construction (n=30)―which were recently conducted by the authors of this paper—suggest that the truth about conspiracy theories is more complex. Given a set of statements about a dramatic historic event (in our case 9/11) that includes official testimonies, allegations to a conspiracy and extremely conspiratorial statements, the majority of participants created a narrative of 9/11 they deemed plausible that might be considered a conspiracy theory. The resulting 30 idiosyncratic stories imply that no clear distinction between official story and conspiratorial narrative is possible any more when the common approach of questionnaires is abandoned. Based on these findings we present a new theoretical and methodological approach which acknowledges conspiracy theories as a means of constructing and communicating a set of personal values. While broadening the view upon such theories, we stay compatible with other approaches that have focused on extreme theory types. In our view, accepting conspiracy theories as a common, regulative and possibly benign phenomenon, we will be better able to understand why some people cling to immunized, racist and off-wall stories—and others do not.